Excesso de estrôncio na fisiologia de Pfaffia glomerata (Spreng.) Pedersen - Costa, Camila Cavalheiro da (2017)
Pfaffia glomerata (Spreng.) Pedersen has been widely used to characterize the physiological and biochemical responses to the excess of various heavy metals, and also for the use in phytoremediation of areas contaminated by heavy metals. Among these, Sr is a metal commonly found in soils and that in high concentrations presents harmful potential to plants.The aimed of this work was characterize two accessions of Pfaffia glomerata (GD and JB) cultivated in five concentrations of strontium (Sr) (0, 1, 2,5, 5 and 10 mM) in solution nutrion. The plants were multiplied in-vitro culture and later carried to the hydroponic system and acclimatized in the solution nutrition for seven days. After this time, concentrations of Sr were added. After 21 days of culture, growth, biochemical and photossintetic parameters were evaluated. The increase in Sr concentration reduced shoot lenght, number of leaves, root and stems dry mass only in the GD acess. The parameters of roots showed decrease in length, surface area and volume for both acessions. In the shoots, GD access showed higher SOD activity and increased H2O2 and MDA concentrations, but decreased chlorophyll a, chlorophyll b, total chlorophyll and carotenoid concentrations. The JB access showed an increase in the concentrations of H2O2 and MDA in the highest concentration of Sr and only in the concentration of 2,5 mM of Sr there was a greater accumulation of chlorophyll a and chlorophyll b. In the roots it was observed that in the GD access increased SOD activity with the increase of the Sr concentration and for the JB access only in the concentration of 2,5 mM of Sr, an increase in the concentration of SOD was observed. The H2O2 concentration increased for the GD access and decreased in the JB access. The concentration of MDA reduced in the GD access and for JB access there was a reduction in the concentration of 5 mM of Sr. It was also observed changes in the photosynthetic process of the GD access, mainly in the higher concentration of the element, causing reduction in the net assimilation rate of CO2, stomatal conductance, intercellular CO2 concentration, transpiratory rate and carboxylation efficiency of rubisco. GD acess showed the highest changes in the analyzed parameters and the JB access was more tolerant to high concentrations of Sr in the nutrient solution than the GD access, which showed a reduction of growth in the highest concentration of Sr (10 mM).